Electrochemical immunosensor based on gold-thionine for detection of subarachnoid hemorrhage biomarker - Wang, Mengyue; Gao, Feng; Ni, Shoujie; Song, Yanan; Wang, Cai; Li, Qian; Zhao, Peng (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: In clinical work, the realization of an early diagnosis of Subarachnoid hemorrhage (SAH) is primarily based on conventional computed tomography (CT), MR angiography, transcranial Doppler (TCD) ultrasound, and neurological assessments. However, the association between imaging manifestations and clinical findings is insufficiently perfect, particularly in SAH patients in acute phases with a lower amount of blood. The establishment of a direct, rapid and ultra-sensitive detection method based on electrochemical biosensors has emerged as a new competitive challenge in disease biomarkers research. Methods: In this study, a novel free-labeled electrochemical immunosensor for rapidly and sensitively detecting IL-6 in subarachnoid hemorrhage (SAH) blood has been developed using Au nanospheres-thionine composites (AuNPs/THI) as the interface modified on the electrode. Then, we detected IL-6 in blood samples from SAH patients by (enzyme-linked immunosorbent assay) ELISA and electrochemical immunosensor. Results: Under the best conditions, the developed electrochemical immunosensor exhibited a wide linear range from 10−2 ng/mL to 102 ng/mL with a low detection limit of 1.85 pg/mL. Furthermore, when the immunosensor was employed in the analysis of IL-6 in 100% serum, the results obtained by electrochemical immunoassay were consistent with those obtained by ELISA without suffering from other significant biological interference. Discussion: The designed electrochemical immunosensor realizes the detection of IL-6 in actual serum samples with high accuracy and sensitivity, and could potentially become a promising technique for applications in the clinical diagnosis of SAH.